Comparative study of the toxic effects of polystyrene microplastic particles of different sizes on the livers of pearl gentian grouper (Epinephelus fuscoguttatus♀ × E. lanceolatus♂) - Hongyue Shi; Meichen Liu; Xiaohan Yang; Yijiang Luo; Zhenzhen Fang; Yanbin Ji; Chengxun Chen; Yanli Liu; Xueliang Sun; Wenwen Yu (Marine Pollution Bulletin, 2026)

Insights into the pH-driven emulsifying properties and self-assembly behaviour of pea peptides - Xiaoyang Sun; Yan Chen; Xinxin Xu; Pei Wang; Jinhu Tian; Meichen Liu; Xiufeng Zhang; Xiaoqing Yuan; Fusheng Chen; Lifen Zhang (Food Research International, 2026)

Hyperspectral monitoring of wheat gluten index based on multi-model ensemble and adaptive learning - Shiyou Zhu; Juan Bai; Yulong Chen; Jingyu Chen; Caiyu Ji; Yingchao Hao; Sha Yang; Yu Zhao; Meijun Zhang; Meichen Feng; Wude Yang; Guangxin Li (Food Chemistry, 2026)

Decoupling of arbuscular mycorrhizal fungi and soil organic carbon under nitrogen addition in terrestrial ecosystems: a meta-analysis - Andi Li; Jing Chen; Senhao Wang; Guangcan Yu; Meichen Xu; Anchi Wu; Jinhua Mao; Wei Zhang; Zhanfeng Liu; Juxiu Liu; Jiangming Mo; Mianhai Zheng (Frontiers of Earth Science, 2026)

Hyperspectral estimation on the photosynthetic phenotype of winter wheat under drought stress using machine learning algorithms - Yanxia Chen; Xiaobin Yan; Tingyue Huo; Yuchao Yang; Bei Tie; Chenhao Qin; Meichen Feng; Xingxing Qiao; Xiaokai Chen; Guangxin Li; Chao Wang; Wude Yang (Precision Agriculture, 2026)

Integrating leaf-scaled spectra and machine learning for rapid estimation of photosynthetic phenotypes across soybean genotypes - Chao Wang; Xiaobin Yan; Yan Bai; Jiaxue Zhang; Xinhui Guo; Xiaomei Zhang; Meichen Feng; William Rickard; Yu Zhao; Fangzhou Li; Chenbo Yang; Xiaokai Chen; et al. (Computers and Electronics in Agriculture, 2025)

Monitoring the growth status of winter wheat by using the machine learning algorithm and the fusion of spectral and texture features derived from the UAV remote sensing - YiMing Su; XiaoBin Yan; Hao Li; ZiHao Liang; ShuangMei Zhao; Ping Chen; Zhen Zhang; XingXing Qiao; Yu Zhao; MeiChen Feng; Fahad Shafiq; XiaoYan Song; et al. (Computers and Electronics in Agriculture, 2025)

An integrated CFD and CNN-GRU approach for accurate prediction of PM2.5 in greenhouse environments of Northeast China - Shuo Zhang; Li Guo; Haiye Yu; Bo Zhang; Meichen Chen; Lei Zhang; Dawei Li; Yuanyuan Sui (Building and Environment, 2025)

Plant morphological and physiological traits are stable in a nitrogen-saturated tropical forest after 18-year nitrogen additions - Guangcan Yu; Jing Chen; Andi Li; Senhao Wang; Liang Song; Xianmeng Shi; Junhua Yan; Meichen Xu; Yuewei Xue; Xiankai Lu; Wei Zhang; Juan Huang; et al. (Plant and Soil, 2025)

Magnetic properties of agricultural soils and their relationships with environmental factors in Jinghong, Yunnan, China - Meichen Wang; Haixia Li; Shiyu Li; Yudong Chen; Gangqiang Li (Earth Science Informatics, 2025)

The application of marine bioactive composite materials in environmental remediation - Yanan Huang; Hao Li; Ronglian Xing; Xiaorui Chen; Yuxin Sun; Meichen Tian; Ran Zhang; Xin Wang; Xinxin Wang; Rui Li; Lihong Chen; Hongxia Zhang; et al. (Desalination, 2025)

Radiomics-based Modelling Unveils Cerebellar Involvement in Parkinson’s Disease - Yini Chen; Yiwei Qi; Yiying Hu; Tao Qiu; Meichen Liu; Qiqi Jia; Yubing Sun; Xinhui Qiu; Bo Sun; Zhanhua Liang; Weidong Le; Tianbai Li (The Cerebellum, 2025)

Photolysis of p-phenylenediamine rubber antioxidants in aqueous environment: Kinetics, pathways and their photo-induced toxicity - Chen Wang; Meichen Sun; Minghui He; Siyu Zhao; Meinuo Lv; Xiaotian Xu; Chunbei Ye; Linjing Li; Limin Su; Yuanhui Zhao (Journal of Hazardous Materials, 2024)

Changes in the magnetic properties of a tropical red soil following the conversion of forest into agricultural land - Meichen Wang; Fengrui Li; Haixia Li; Xiaoling Zhang; Shiyu Li; Gangqiang Li; Yudong Chen; Yang Wang; Jingyuan Hu; Junmin Ye (Journal of Applied Geophysics, 2024)

Dietary bile acids inclusion improves dietary carbohydrate utilization, antioxidant capacity and intestinal microbiota and inflammation of largemouth bass (Micropterus salmoides) - Wenfei Li; Ye Gong; Ning Liu; Shiwen Chen; Meichen Yue; Jinbao Li; Xuxiong Huang; Naisong Chen; Songlin Li (Aquaculture, 2024)

Metagenomic analysis towards understanding the effects of ammonia on chain elongation process for medium chain fatty acids production - Zheng Chen; Zhijian Shi; Yalei Zhang; Yan Shi; Meichen Sun; Yong Cui; Shicheng Zhang; Gang Luo (Bioresource Technology, 2024)

A new flavonoid glycoside from Toxicodendron vernicifluum (Stokes) F.A. Barkley - Chengye Zhao; Meichen Li; Yuqian Yang; Minni Qin; Ruojia Wang; Qing Zhu; Guangtong Chen; Andong Wang (Natural Product Research, 2023)

Molecular insights into the impacts of acid mine drainage on dissolved organic matter dynamics in pit lakes - Zhixiang She; Jin Wang; Chen He; Zhengfeng Jiang; Xin Pan; Meichen Wang; Ding Ma; Quan Shi; Zhengbo Yue (Science of The Total Environment, 2023)

Spatiotemporal characteristics and influencing factors of net primary production from 2000 to 2021 in China - Chen Yang; Guohui Zhai; Meichen Fu; Chang Sun (Environmental Science and Pollution Research, 2023)

Does green transformation trigger green premiums? Evidence from Chinese listed manufacturing firms - Yuzhen Chen; Xiaojun Ma; Xuejiao Ma; Meichen Shen; Jingquan Chen (Journal of Cleaner Production, 2023)

Genome-centric metagenomic analysis revealed the microbial shifts in response to long-chain fatty acids (LCFA) in anaerobic digestion with hydrochar - Meichen Sun; Chao Zhang; Zhijian Shi; Chen Zhang; Shicheng Zhang; Gang Luo (Chemical Engineering Journal, 2023)

Isolation of a new monoterpenoid glycoside from Anhua dark tea based on an NMR-guided method and its cytotoxic activity against MDA-MB-231 and SH-SY5Y cell lines - Yunqiang Zhang; Jianyu Liu; Miao Chen; Yanhua Fan; Meichen Li; Andong Wang; Gaigai Liu; Yongnan Xu; Xuhong Ren; Yan Xiao (Natural Product Research, 2022)

Risks Assessment Associated with Different Sources of Metals in Abandoned Soil of Zhuxianzhuang Coal Mine, Huaibei Coalfield (Anhui, China) - Hongxia Fang; Herong Gui; Jun Li; Hao Yu; Meichen Wang; Yaqi Jiang; Chunlei Wang; Chen Chen; Yaru Zhang; Yiheng Huang (Bulletin of Environmental Contamination and Toxicology, 2021)

Comparative transcriptomic and metabolomic analyses of carotenoid biosynthesis reveal the basis of white petal color in Brassica napus - Ledong Jia; Junsheng Wang; Rui Wang; Mouzheng Duan; Cailin Qiao; Xue Chen; Guoqiang Ma; Xintong Zhou; Meichen Zhu; Fuyu Jing; Shengsen Zhang; Cunmin Qu; et al. (Planta, 2021)
Main conclusion The molecular mechanism underlying white petal color in Brassica napus was revealed by transcriptomic and metabolomic analyses. Abstract Rapeseed ( Brassica napus L.) is one of the most important oilseed crops worldwide, but the mechanisms underlying flower color in this crop are known less. Here, we performed metabolomic and transcriptomic analyses of the yellow-flowered rapeseed cultivar ‘Zhongshuang 11’ (ZS11) and the white-flowered inbred line ‘White Petal’ (WP). The total carotenoid contents were 1.778-fold and 1.969-fold higher in ZS11 vs. WP petals at stages S2 and S4, respectively. Our findings suggest that white petal color in WP flowers is primarily due to decreased lutein and zeaxanthin contents. Transcriptome analysis revealed 10,116 differentially expressed genes with a fourfold or greater change in expression ( P -value less than 0.001) in WP vs. ZS11 petals, including 1,209 genes that were differentially expressed at four different stages and 20 genes in the carotenoid metabolism pathway. BnNCED4b , encoding a protein involved in carotenoid degradation, was expressed at abnormally high levels in WP petals, suggesting it might play a key role in white petal formation. The results of qRT-PCR were consistent with the transcriptome data. The results of this study provide important insights into the molecular mechanisms of the carotenoid metabolic pathway in rapeseed petals, and the candidate genes identified in this study provide a resource for the creation of new B. napus germplasms with different petal colors.

Occurrence and distribution of selected antibiotics in the surface waters and ecological risk assessment based on the theory of natural disaster - Sijia Li; Hanyu Ju; Jiquan Zhang; Peng Chen; Meichen Ji; Jianhua Ren; Shuyun Zhao (Environmental Science and Pollution Research, 2019)

The relationship of chromophoric dissolved organic matter parallel factor analysis fluorescence and polycyclic aromatic hydrocarbons in natural surface waters - Sijia Li; Ya’nan Chen; Jiquan Zhang; Kaishan Song; Guangyi Mu; Caiyun Sun; Hanyu Ju; Meichen Ji (Environmental Science and Pollution Research, 2018)